Women's wheelchair basketball lineup analysis at the Tokyo 2020 Paralympic Games: game related statistics explaining team sport performance - Becerra-Muñoz, W.; Wang, J.; Pérez-Tejero, J. (Frontiers in Sports and Active Living, 2023)
Introduction: Performance analysis through game-related statistics in wheelchair basketball (WB) has focused mainly on the study of the individual efficiency of players according to their functional classification. However, there is little evidence focusing on lineup performances (five players on court) and their composition. Thus, the objective of present study was to analyze the efficiency of the women's WB lineups used during the Tokyo 2020 Paralympic Games (PG) and to determine the variables that best discriminated the lineup performances according to the final point differential.